المدير الليبي دراسة تطبيقية - Buera, Abu Bakr (Dirasat in Economics and Business, 1977)
Within the past decade or so the field of business management has been marked with a strong trend of multinationalism. As managers are the agents who implement such business philosophies their study becomes indespensable. Despite this important role managers play, enough attention has been paid to them only in areas such as the United States and, although to a lesser degree, Western Europe. The greatest lack of information about managers manifests itself in the developing countries. Ironically, it is this part of the world where the role of managers is desparately needed to gear up the development process